Harnessing Corn Silk Syrup For Liver And Kidney Health: A Natural Cure - Sharma, Rishab; Prince, Prince; Ranaut, Ashish; Sharma, Aditya; Thakur, Mayank; Thakur, Shailly; Akash, Akash; Patial, Ripul; Abrol, Suryansh; Chauhan, Harsh; Devi , Anjana (Journal of Neonatal Surgery, 2025)
Traditional herbal remedy Zea mays L. (commonly known as corn silk) is now scientifically proven to benefit liver and kidney health. This analysis investigates both the chemical identities present in corn silk syrup and its clinical effects together with its multiple therapeutic usage possibilities as an eco-friendly natural medicine. The bioactive contents in corn silk include flavonoids, saponins, alkaloids, phenolic compounds that generate its strong hepatoprotective along with anti-inflammatory and diuretic effects and antioxidant potential. These properties make corn silk particularly promising in managing renal and hepatic disorders such as nephrotoxicity, kidney stones, and liver fibrosis. Preclinical and limited clinical studies suggest that corn silk syrup may reduce elevated serum creatinine and urea levels, enhance urine output, and protect against drug- or toxin-induced hepatic damage. Its antioxidant activity contributes to the reduction of oxidative stress and liver and kidney tissue lipid peroxidative damage. In addition, the preparation of the syrup using green and simple extraction techniques underpins its incorporation into functional food and nutriticum capsules. Further standardization of dosage, long-term evaluation of safety, and clinical trials are needed to confirm its efficacy and optimize its use. This review brings the potential of the use of corn silk syrup as a cheap, natural alternative or addendum to the liver and kidney health management process